PENGARUH LOGISTICS SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN JASA KURIR DI KANTOR POS BATURAJA - Hendri, Hendri; Fifian Permata Sari; Munajat, Munajat (Media Bina Ilmiah, 2025)
This study aims to analyze the effect of logistic service quality on customer satisfaction of courier services at the Baturaja Post Office. The method used in the study is an explanatory method using 100 consumer samples in the analysis. The data analysis used is multiple linear regression analysis. The results of the analysis show that Timeliness, Accuracy of Order, Quality of Information, and Quality of Contact Personnel simultaneously have a positive and significant effect on customer satisfaction of courier services at the Baturaja Post Office. Timeliness, Accuracy of Order, Quality of Information, and Quality of Contact Personnel partially have a positive and significant effect on customer satisfaction of courier services at the Baturaja Post Office.